2017
DOI: 10.1016/j.ijcard.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of microvascular dysfunction in patients with microvascular angina

Abstract: Patients with MVA can be characterized by microvascular glycocalyx dysfunction using sublingual microscopy. The strong correlation between sublingual PBR responsiveness and myocardial perfusion reserve suggests that the glycocalyx may play an important role in the regulation of microvascular volume for myocardial perfusion and supports the concept of impaired glycocalyx barrier properties in MVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Sublingual areas either on the left or right side of the frenulum gave identical results in repeated estimations . The applications of the method to various clinical studies have been extensively validated in a number of recent publications …”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Sublingual areas either on the left or right side of the frenulum gave identical results in repeated estimations . The applications of the method to various clinical studies have been extensively validated in a number of recent publications …”
Section: Methodsmentioning
confidence: 87%
“…12 The applications of the method to various clinical studies have been extensively validated in a number of recent publications. [13][14][15][16]…”
Section: Perfusion Of Sublingual Endothelial Glycocalyxmentioning
confidence: 99%
“…Patients at increased cardiovascular risk show endothelial glycocalyx and microvascular perturbations [1][2][3]. This condition has been advocated as a determinant of microvascular angina [4]. Patients with coronary disease have activated circulating platelets, a decreased platelet reactivity and an elevated platelet adhesion [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…SDF video image analysis with automated data capture is one of the principal methods to assess microvascular health noninvasively in vivo. This instrument measures the degree to which red blood cells (RBC) access (radially penetrate) the sublingual microvascular glycocalyx, and is based on the concept that RBCs can penetrate deeper toward the endothelium when the glycocalyx is damaged or unstable (functionally thinner) (Dane et al, ; Ikonomidis et al, ; Jaarsma et al, ; Lee et al, ; Mulders, Nieuwdorp, Stroes, Vink, & Pinto‐Sietsma, ; Xue, Jiang, Chen, & Chen, ). This RBC accessible portion of the glycocalyx is commonly termed the perfused boundary region (PBR).…”
Section: Introductionmentioning
confidence: 99%
“…However, a considerably wider variation in PBR's was observed in patients with obstructive CAD such that they did not differ from either controls or patients with angina. The authors suggested that this may reflect heterogeneity of microvascular dysfunction, or even the absence of microvascular dysfunction in a subset of patients with obstructive CAD (Jaarsma et al, ). In contrast, Mulders and coworkers found an increased PBR in patients with premature CAD and a family history of premature cardiovascular disease, and their first degree families members with elevated coronary artery calcification (Mulders et al, ).…”
Section: Introductionmentioning
confidence: 99%